IMPLEMENTASI PEMBELAJARAN KOLABORATIF MENGGUNAKAN BREAKOUT ROOM ZOOM MEETING PADA PEMBELAJARAN JARAK JAUH - FARAH FAUZIAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study was conducted to determine the effect of Collaborative learning strategies in online learning during distance learning. The method used is an experiment with a pretest-posttest research design. The online media used is the zoom meeting application. There are two groups, namely the experimental group and the control group which were selected randomly and have been tested for normality and homogeneity tests. The experimental group is the group that is given a collaborative learning strategy, while the control group uses the conventional method. The data analysis technique used is a test technique. Based on the results of the study, the N-gain score of the experimental group (collaborative) was 63.6904 or 63.7% and was categorized as quite effective. The average normalized gain (N-gain) of the experimental group students' learning outcomes was 0.63 which was included in the medium category. This means that the application of collaborative learning strategies is sufficient to improve student learning outcomes on the subject of Ideas and Business Opportunities in class X SMAN 82 Jakarta. ABSTRAKPenelitian ini dilakukan untuk mengetahui pengaruh strategi pembelajaran Kolaboratif dalam belajar online pada saat pembelajaran jarak jauh. Metode yang digunakan adalah eksperimen dengan desain penelitian pretest-posttest. Media Online yang digunakan adalah aplikasi zoom meeting. Terdapat dua kelompok yaitu kelompok eksperimen dan kelompok kontrol yang dipilih secara acak serta telah dilakukan uji normalitas dan uji homogenitas. Kelompok eksperimen adalah kelompok yang diberikan strategi pembelajaran kolaboratif, sedangkan kelompok kontrol menggunakan metode konvensional. Teknik analisis data yang digunakan adalah teknik tes. Berdasarkan hasil penelitian diperoleh N-gain score kelompok eksperimen (kolaboratif) adalah 63,6904 atau 63,7% dan masuk dalam kategori cukup efektif. Rata-rata gain ternormalisasi (N-gain) hasil belajar peserta didik kelompok eksperimen adalah 0,63 yang termasuk kategori sedang. Artinya penerapan strategi pembelajaran kolaboratif cukup dapat meningkatkan hasil belajar peserta didik pada pokok bahasan Ide dan Peluang Usaha di kelas X SMAN 82 Jakarta.